Rembrandt’s The Standard Bearer: New Findings from Imaging Analyses - Noble, Petria; Van Loon, Annelies; Bikker, Jonathan (The Rijksmuseum bulletin, 2023)
Petria Noble, along with Annelies van Loon and Jonathan Bikker, examined the paint application and composition in Rembrandt's The Standard Bearer and concluded that some pigments used for the costume have lost their colour; however, the white flag is as intended. It is also now clear how the artwork was restored in 1958.